CONTEXTUAL LEARNING FOR BASIC EDUCATION: THE HISTORY AND PHILOSOPHY - Maemonah Maemonah; Siti Anisatun Nafi'ah (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
Discourse models or contextual approaches as part of the learning concept, which is still dwelling on the dimension of implementation either in the context of certain subjects or in the context of a particular class or school. Such in current conditions the assumption from educators’ scopes that contextual learning as something perfect, independent and in accordance with the present reality. The limitation of understanding gives impact to a closed mind. By those reasons, this paper seeks to explore the idea of ​​contextual learning or which is often called as Contextual Teaching and Learning (CTL) both in terms of historical and philosophical dimensions. Based on the historical approach, contextual learning as a solution as well as a criticism of the stagnation of the constructivism flow in the face of global competition in the third era nowadays. However, the root of pragmatism is very strong in contextual learning. Therefore, in terms of philosophy, the discourse of contextual learning has been focused on the issue of education substance rather than the education values so that in the realm of its application in Indonesia, contextual learning should be given a critical note to be truly in accordance with the culture and behavior of Indonesian society.